LSD: Mechanisms and relevance to the treatment of depression - Bouloufa, Amel; Delcourte, Sarah; Delannay, Thomas; Rovera, Renaud; Lau, Thorsten; Mouledous, Lionel; Dkhissi-Benyahya, Ouria; Guiard, Bruno P.; Haddjeri, Nasser (Neuroscience & biobehavioral reviews, 2025)
Major depressive disorder (MDD) is one of the most prevalent psychiatric conditions worldwide, affecting over 350 million people. Standard treatments, primarily antidepressants targeting serotonin, noradrenaline, and/or dopamine, are based on the monoamine hypothesis, which links depression to imbalances in these neurotransmitters. A sizable fraction of patients, however, does not get enough relief, which highlights the limits of current drug treatments. Treatment-resistant depression (TRD), a mainly intractable subtype of MDD, affects around 30% of MDD sufferers, therefore it is imperative that better effective therapies be found. Recent research has focused on psychedelic medicines including lysergic acid diethylamide (LSD), which affects serotonergic as well as glutamatergic systems. These drugs have demonstrated potential to induce rapid and long-term antidepressant responses, possibly by the facilitation of neuroplasticity and adjustment of long-term neural communication, even after the drug is cleared from the body. Ongoing clinical trials are testing the efficacy and safety of LSD in TRD and simultaneously resolving problems of placebo design and risk minimization. This narrative review examines the neurobiological mechanisms of LSD, assesses its potential as an antidepressant and anxiolytic agent, and discusses the safety issues associated with its utilization. Although still experimental, psychedelic therapies could demonstrate a significant shift in psychiatric treatment, offering new hope for patients who have not responded to conventional antidepressants. Sustained research is essential to validate these results and guide their integration into clinical practice.